Chrestomathia: arte e ciência para Jeremy Bentham - Otaviani, Márcia Cristina (2012)
Jeremy Bentham (1748-1832) was an English philosopher who lived during the eighteenth and nineteenth centuries, a period when major events occurred in the world, not only on philosophical grounds, but also in economic and apart from being entitled as the "founder" utilitarian school, and suggest new ideas about moral issues and legislation, Bentham also brought new perspectives and solutions to issues such as education. In the book named Chrestomathia, Bentham exposes your beliefs about how teaching should be done in a standard school, the School Chrestomathia as its name. The main function of the school would be to promote greater quantity and better quality of knowledge and, consequently, wellness for all involved. It is in this work that he presents he believed to be the more correct way to categorize and divide the different areas of knowledge. In this work we aim to show how the Tree of Knowledge that he proposed is built, showing the intimate connection with teaching, and also trying to analyze the ideas behind their proposals, as well as the criticism that the author makes to the current way of classifying the human knowledge